THE INFINITE MODEL: MOBILE PAYMENT CONTINUANCE INTENTION - Yusuf, Abdul; Hurriyati, Ratih; Disman, Disman; Hendrayati, Heny; Hidayat, Yosep (Faculty of Economic and Business, University of Pasundan, 2026)
This study investigates the factors influencing users' continuance intention (CI) in fintech mobile payment services, particularly in the post-COVID-19 era. With the rapid adoption of digital payment methods, the research examines key determinants such as perceived usefulness, perceived ease of use, trust, security and privacy, satisfaction, and habit. An explanatory quantitative research design was employed, analyzing data from 101 respondents. The results reveal that habit and satisfaction are the primary drivers of continuance intention, while traditional factors such as ease of use and trust become less significant in the post-adoption phase. These findings challenge established models and highlight the shift in user behavior towards habitual use and emotional satisfaction. This study contributes to the literature by offering an integrated model for understanding user retention in the fintech sector and provides practical insights for fintech providers to enhance customer engagement and foster long-term loyalty.